Four species of the sakaiella group of Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) from China - Min, Qiuyue; Li, Houhun; Wang, Shuxia (Zootaxa, 2026)
Three new species of the genus Promalactis Meyrick, 1908 are described: P. bifolia Wang sp. nov., P. maoxianensis Wang sp. nov., and P. serpentina Wang sp. nov. The female of P. spiniflagellata Wang, 2019 is reported for the first time. Diagnostic characters to distinguish the new species from their allies are provided. Images of adults and illustrations of genitalia are included.